To study the association of CSF leaks in open and closed FrontoBasal Skull Fractures - Pandurang Barve; Vinayak Raje; Sunil Yadav; Vaishali Raje; Raunaq Chhabra; Trishant Chotai; Devdutt Patil (Al Ameen Medical College, 2017)
Objective: To study the association of CSF leaks in open and closed Frontobasal skull fractures. Background: Frontobasal skull fractures are a complex entity. CSF leak is common after such injuries. This study examines the relationship between occurrence of CSF leak and different type of frontobasal skull fractures. Methods: A prospective study was conducted from November 2014 to May 2016 in patients admitted with head injuries to KIMSDU, Karad, Maharashtra. All data was retrieved using a standardized data collection form. Results: Out of the total 55 patients of frontobasal fracture, 39(70.9 %) were found to have CSF leak. Out of these 55, 52 (94.5%) were males and 3 (5.5 %) were females. The mean age of patients with head injury was found to be 36.5± 13.83 years. Out of 55 patients, 43 patients had GCS 12-15, 9 had 7-11and 5 had <7. Out of 39 patients, 30 patients (54.5%) had closed skull fracture and 9 patients (16.4%) had open skull fracture. Statistical analysis showed no significant association between type of skull fracture and presence of CSF leak (p> 0.05). Conclusion: No significant association was found between the occurrence of CSF leak and different types of frontobasal skull fractures. Most cases were treated conservatively.